The Case of Tick-borne Spotted Fever in a Child Arriving from the Crimea - N. Zvereva N.; M. Saifullin A.; L. Karan S.; V. Larichev F.; A. Butenko M.; M. Bazarova V.; R. Saifullin F.; S. Smetanina V.; Н. Зверева Н.; М. Сайфуллин А.; Л. Карань С.; В. Ларичев Ф.; et al. (CHILDREN INFECTIONS, 2018)
A case of Tick-borne spotted fever in a child after a visit to an endemic region, the Republic of Crimea, is described. The disease caused difficulty in terms of clinical diagnosis, which led to the delayed prescription of specific therapy with doxycycline. The diagnosis of Тick-borne spotted fever was made on the basis of detecting R. conorii DNA in a washout with primary affect. In the course of the disease, IgM class antibodies were detected during serological analysis of paired serum. Приводится описание случая клещевой пятнистой лихорадки у ребенка после посещения эндемичного региона — республики Крым. Заболевание вызвало затруднение в плане клинической диагностики, что привело к отсроченному назначению специфической терапии доксициклином. Диагноз клещевой пятнистой лихорадки был поставлен на основании выявления ДНК R. conorii в смыве с первичного аффекта. В динамике заболевания были выявлены антитела класса IgM при серологическом исследовании парных сывороток крови.